2016
DOI: 10.1177/1356336x16681955
|View full text |Cite
|
Sign up to set email alerts
|

Comparing teaching approaches in two student-designed games units

Abstract: Comparing teaching approaches in two student-designed games units 1 Comparing teaching approaches in two student-designed games unitsStudent-designed games have been referred to in many different ways in the literature, including games making (Almond, 1983;Cox and Ledingham, 1988), child-designed games (Rovegno and Bandhauer, 1994), games invention (Curtner-Smith, 1996), and inventing games (Butler and Hopper, 2011). Although there may be slight discriminations between each of these terms, they are all part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…It can be suggested that compromising helped strengthen most groups' affiliation, resulting in absence of disengagement. These findings are consistent with previous SDG studies (André & Hastie, 2016;, where students' commitment to work together as a group helped to enhance their engagement.…”
Section: Engagementsupporting
confidence: 91%
See 2 more Smart Citations
“…It can be suggested that compromising helped strengthen most groups' affiliation, resulting in absence of disengagement. These findings are consistent with previous SDG studies (André & Hastie, 2016;, where students' commitment to work together as a group helped to enhance their engagement.…”
Section: Engagementsupporting
confidence: 91%
“…Positive social interactions, improved social skills, peer acceptance, and cooperation are potential outcomes of students' engagement of collaborative groups (Hastie, 2010). Although SDG has been known since the late 1960's (Mauldon & Redfern, 1969), only in the past few years it has been supported with research findings (André, Hastie & Araújo, 2015;André & Hastie, 2016;Butler, 2013;Casey, Hastie, & Rovegno, 2011;Hastie & André, 2012;Hastie & Casey, 2010).…”
Section: Student-designed Games: a Rising Teaching Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that students can be successfully educated in the SDGs requires specific curricular programming [58]. The importance of this was noted by André and Hastie [86], who reported the significant advantages of SDG programs based on technologies, as they are required to complement face-to-face learning. The observation is consistent with what was reported by Naik et al [87].…”
Section: Discussionmentioning
confidence: 99%
“…The PE teachers participating in this study believed that blended learning implied extra work compared to fully face-to-face instruction. Previous published hybrid PE experiences agree with this perception, as teachers reported that the use of online tools for teaching and the added online interaction with students were time-demanding and resulted in increased out-of-class workload [15,33,34]. During the first wave of the COVID-19 pandemic, a group of students in initial training to become teachers expressed their concerns about the increased probability of suffering from teacher stress when following an online teaching methodology [35].…”
Section: Discussionmentioning
confidence: 82%